Local innovation for improving primary care cardiology in resource-limited African settings: an insight on the Cardio Pad® project in Cameroon - Noubiap, Jean Jacques N.; Jingi, Ahmadou M.; Kengne, André Pascal (Cardiovascular Diagnosis and Therapy, 2014)
Cardiovascular disease (CVD) is an emerging threat to the health of populations in Africa. With the inadequate health infrastructures, understaffed and underfunded health systems, African countries are ill-prepared to cope with the increasing demand for care for CVD, particularly for populations in remote and underserved rural areas, where 60% of the population currently reside. Task shifting and telehealth have been suggested as strategies to overcome the current health workforce shortage in African countries, and to increase access to prevention and curative services for emerging CVD. However, strategies for promoting their incorporation into the existing health systems, have yet to be developed. The Cardio Pad® initiative (originating from Cameroon) seeks to provide appropriate solutions to improve the application of telemedicine for CVD prevention and control in remote African settings. The Cardio Pad® is a telecardiology device which provides a number of advantages in terms of cost, ease of use, autonomy and reduced technology requirements. It is a fully touch screen medical device which enables cardiac tests such as electrocardiograms (ECG) to be performed in remote underserved areas (rural areas for instance), while the test results are transferred wirelessly via mobile phone connection, to specialist physicians who can interpret them and provide assistance with case management. While most of the current telemedicine clinical services on the African continent receive most expertise from developed countries, the Cardio Pad®, a local invention by a 26-year-old Cameroon-trained engineer demonstrates how much innovative solutions to combat CVD and other health issues could and should be developed locally in Africa.